Boosting Students’ Reading Comprehension Skill Using Multimodal Descriptive Texts Based Google Site - Siti Mariam; Catur Kepirianto; Sayyidatul Fadlilah; Priyono; M. Sholahuddin (ELITE JOURNAL, 2023)
This study aims at explaining the implementation of using multimodality learning materials based Google Site to boost students’ reading comprehension of descriptive texts. Secondly, to describe students’ engagement of using these digital reading materials. It employed qualitative method. The research design was classroom action research which applied two cycles. The research participants were 40 of the third semester students of Arabic Education department at Islamic university in Indonesia in the academic year of 2022/2023. Data collection techniques used interview, observation, pre-test and post-test. The results of this study show that there is an improvement in every cycle of students’ reading comprehension competence. They also enjoyed and enthusiastic in joining this reading class. It is recommended that multimodal descriptive text based Google Site can boost students’ reading comprehension skills. Keywords: descriptive text, google site, multimodality, reading comprehension